(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Callus cultures of alkanet (Alkanna orientalis) of leaf, root and stalk origin able to synthesize naphthoquinones are obtained. Increase of cytokinin content in the nutrient medium promotes to synthesize pigments’ quantity rising. In callus culture of root origin by means of HPLC the shikonin was identified.